Respiratory Distress of Newborn dengan Pemantauan Respirasi dan Alih Baring untuk Mengatasi Hiperbilirubinemia di Ruang Neonatal Intensive Care Unit: Studi Kasus - Musfirah; Kadek Ayu Erika; Rifka Zulfiani Latinapa; Abdul Kadir (Journal of Bionursing, 2022)
Respiratory Distress of Newborn (RDN) is a common cause of newborns respiratory distress. The RDN appears within a few hours after birth, and mostly often appears soon after birth. RDN usually has symptoms of tachypnea with a respiratory rate of more than 60 breaths per minute accompanied by grunting, chest retractions, nostril breathing, and cyanosis. Asphyxia is one of the causes of RDN. In addition, asphyxia can cause an increase in bilirubin levels in newborns leading to hyperbilirubinemia. This study was to observe the patient's breathing pattern and bilirubin levels among infants with RDN. A descriptive study, specifically case study design was utilized. The subject of this case study was baby H who diagnosed with RDN with CPAP installed on the 4th day. Results showed that monitoring vital signs for 3 days can improve breathing patterns and prevent respiratory failure. Meanwhile, phototherapy along with bed transfer has been shown to reduce bilirubin levels from bilirubin levels before the intervention, namely 20.65 mg/dl to 7.57 mg/dl after the intervention. Respiratory monitoring can improve respiratory rate. In addition to phototherapy, infants can also be given bed rest while monitoring vital signs to treat hyperbilirubinemia in RDN infants.